National programmes of specialists training - fast track of the specialists reserve creation - Абросимова, Елена Борисовна (Technology audit and production reserves, 2014)
The issues of training specialists, namely low, mid and top-level managers, implementing enterprises and organizations development programs under the State Plan for management training for the national economy of the Russian Federation are considered in the paper. The reasons for the Programme popularity among listeners and employers were identified. The main objective of the study is to assess the reasons for the President’s programme popularity among managers of companies - Programme listeners and heads of sending organizations as the fastest way for professional development and training of specialists reserve for the innovation economy, respectively. The analysis of results of the sociological survey of listeners of educational programs, implemented under the State Plan for management training for the national economy of the Russian Federation in the Nizhny Novgorod branch of the Federal State Autonomous Educational Institution of Higher Professional Education "National Research University "Higher School of Economics" (NRU HSE - Nizhny Novgorod), and representatives of the sending organizations is given in the paper. Following the survey results it can be concluded on the Programme’s ability to meet the requirements of specialists reserve training for the innovation economy. The research results can be applied in developing practice-oriented specialists training programs and for selecting educational trajectories at continuous managers training for rapid specialists reserve formation.